Alternanthera repens and Bidens odorata, Resilience Medicinal Plants in Mexico City - Astudillo Vázquez, Adela; Dávalos Valle, Hortencia; Patiño Siciliano, Alfredo (Revista de Ciencias, 2015)
In Mexico, the use of medicinal plants to treat health disorders has been practiced since pre-Columbian times. Unfortunately, this knowledge has been lost over time, mainly in highly urbanized  areas. We conduct an ethnobotanical survey about Alternanthera repens, Kuntze (Amaranthaceae) and Bidens odorata Cav. (Asteraceae) in Mexico City. A total of 500 peope were interviwed, 250 of them were questioned about B. odorata and 250 in relation  to A. repens, the questions included: common names, medicinal uses, part of the plant used, mode of preparation, route of administration and duration of treatment. This study revealed that both plant species are currently used in top diseases, in the study area, mostly to treat gastrointestinal disorders, specifically diarrhea; A. repens is also recommended to treat fever and renal diseases, whereas B. odorata is used for treating diabetes, renal disorders and less frequently for fever and as forage. The results allow us to ensure that these plants are used today and are potentially important to continue with the determination of their pharmacological effects and other aspects.